Pengembangan Pembelajaran Bahasa Arab di TPA Nurul Hidayah Desa Mulyamekar Babakancikao Purwakarta: Pengembangan Pembelajaran Bahasa Arab - GUNAWAN GUNAWAN; Taufik Luthfi (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This Dedication about "Development of Arabic Learning at TPA Nurul Hidayah" is motivated by the importance of learning Arabic from an early age as well as the understanding that must be obtained by students, Arabic learning must be carried out in a way that is varied but also effective so that Arabic learning can be achieved. easily digested and accepted by students, one of them is by using the ghina method or singing. The singing method is a learning method that uses sung poems. Usually these poems are adapted to the materials that will be taught by educators. According to some experts, singing makes the learning atmosphere cheerful and passionate so that children's development can be stimulated more optimally. With these benefits, the devotees improvise the singing method for the improvement and development of Arabic learning. This research and service uses a qualitative-descriptive method with a process of observation, implementation (learning) and evaluation. and the result is a fairly large increase in the development of understanding and memorization of students, hopefully the results of this service will provide many benefits for the development of Arabic, especially in TPA Nurul Hidayah.